2019
DOI: 10.1002/bab.1732
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme production by solid‐state fermentation on soybean meal: A comparative study of conventional and ultrasound‐assisted extraction methods

Abstract: Protease, cellulase, and α-amylase producing Bacillus subtilis strain was cultivated by solid-state fermentation technique using soybean meal as a substrate. The aim of the present study was to establish a highly efficient enzymes' extraction method as a first stage in downstream processing. The conventional extraction procedure was optimized by determining pH, stirring rate, solid/liquid ratio, and time of extraction on enzymes' recoveries from fermented soybean meal. Yields of leached enzymes were compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Although ultrasound is considered a key technology to achieve green chemistry, [ 36 ] the results demonstrated no significant interference of the sonication in extracting the cellulases enzymes group among the adopted values for this variable, a fact that is attributed to the preliminary SLE, which was able to exhaust all the enzymatic content of the fermented medium and partially restricting the sonochemical effects. According to Salim et al, [ 17 ] conventional extraction is preferred when the process aims at obtaining cellulase enzymes in a rapid and concentrated manner. However, a sonication power lower than 1.2 or higher than 1.6 W ml −1 was unfavourable to the process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although ultrasound is considered a key technology to achieve green chemistry, [ 36 ] the results demonstrated no significant interference of the sonication in extracting the cellulases enzymes group among the adopted values for this variable, a fact that is attributed to the preliminary SLE, which was able to exhaust all the enzymatic content of the fermented medium and partially restricting the sonochemical effects. According to Salim et al, [ 17 ] conventional extraction is preferred when the process aims at obtaining cellulase enzymes in a rapid and concentrated manner. However, a sonication power lower than 1.2 or higher than 1.6 W ml −1 was unfavourable to the process.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the conclusion drawn in this study is advantageous because it demonstrated that the UEA was unhelpful in this specific process, unlike in some similar studies. [16,17,35] F I G U R E 1 Response surfaces for enzymatic activity (U ml À1 ) of (A) FPase, (B) CMCase, and (C) β-glucosidase as functions of pH and sonication (W ml À1 )…”
Section: Solid-liquid Extraction (Sle)mentioning
confidence: 99%
See 1 more Smart Citation
“…They can decompose macromolecular polysaccharides into monosaccharide, which are used by animals or provide energy for collaborative microorganisms (Xiong et al, 2016;Olukomaiya et al, 2019). (Feng et al, 2007;Dai et al, 2017;Wang et al, 2017;Cheng et al, 2019;Salim et al, 2019), Lactobacillus plantarum (Mukherjee et al, 2016;Wang et al, 2016;Zhu et al, 2017), Lactobacillus paracasei (Su et al, 2018), Pediococcus acidilactici (Wiseman et al, 2017), Saccharomyces cerevisiae (Zhu et al, 2017), Clostridium butyricum (Su et al, 2018), Bacillus amyloliquefaciens (Yang et al, 2019), Aspergillus niger (Ohara et al, 2018) protease (Cheng et al, 2019;Su et al, 2018;Wang et al, 2017;Yang et al, 2019), acid protease, neutral protease, alkaline protease, cellulase (Salim et al, 2019;Ohara et al, 2018), α-amylase (Salim et al, 2019), xylanase (Wiseman et al, 2017), β-glucosidase (Ohara et al, 2018) Rapeseed (Brassica napus L.) meal Saccharomyces cerevisiae (Chiang et al, 2010), Lactobacillus fermentum, Enterococcus faecium, Bacillus subtilis (Chiang et al, 2010), Aspergillus oryzae (Dossou et al, 2019), Aspergillus niger (Shi et al, 2016;Odinot et al, 2017;Tie et al, 2020) endoglucanase, acid protease (Shi et al, 2016;Tie et al, 2020), feruloyl esterase (Odinot et al, 2017), lignocellulosic hydrolyzing enzymes, phytase (Shi et al, 2016) Cottonseed (Gossypium arboreum L.) meal…”
Section: Substrates Microorganisms Strains and Enzymesmentioning
confidence: 99%
“…At present, most of the technologies of synergism of microbe and enzyme in feed processing comprise one-step fermentation, i.e. simultaneous fermentation of substrate by bacteria in enzyme presence (Ohara et al, 2018;Salim et al, 2019), as shown in Figure 1A. It is worth noting that great changes have occurred in the process parameters when using different strains and enzymes for collaborative treatment.…”
Section: The Technology Of Microbialenzymatic Synergismmentioning
confidence: 99%